Analisis Sub Sektor Perikanan dalam Pengembangan Wilayah Kabupaten Indramayu - Ade Syarief; Eman Rustiadi; Aceng Hidayat (TATALOKA, 2014)
Indramayu regency has a great potential in renewable fisheries. It is expected that this fisheries subsector continues to grow and become a strategic sector in the development of Indramayu regency. The objectives of this research were: (1) to identify the role of the fisheries subsector in the economy of the region and its links with other sectors in Indramayu regency, (2) to learn about the level of development of the regional development of fisheries sub-sector in Indramayu regency based on the conditions of facilities and infrastructure, and (3) to find out the perception of stakeholders in determining development priorities for the fisheries sub-sector as well as to formulate a strategic direction in the development of the fisheries subsector in Indramayu regency. Input-Output analysis showed that the fisheries subsector had not been included in the strategic sector because it had weak inter-sectoral linkages and low multiplier effects of the total economy in Indramayu Regency compared to other economic sectors. Schallogram analysis showed that six sub-districts in the region of hierarchy III were feasible to develop. According to the stakeholders, the priority of fisheries subsector development in Indramayu Regency was the development of aquaculture activities (42.04 %) in terms of improving the quality of human resources (33.66 %). In the development strategy of the fisheries subsector of aquaculture activities in Indramayu regency, priorities should be in the development of existing resources (Natural Resources, Human Resources, Artificial Resource / Infrastructure, Institutional, Technology and Capital) to achieve sustainable development.